Management of mineral resources : creating value in the mining business - Camus, Juan P., 1957- (Society for Mining, Metallurgy, and Exploration, 2002)
The mining industry's strategy for coping with low profitability has focused primarily on controlling production costs. Despite mechanization, automation, and other technical improvements, the aggregate profitability of mining still falls far short of that realized by most other industries. Author Juan Camus contends that what is required is not additional technical knowledge, but rather sound management practices that utilize the existing knowledge base more productively. Management of Mineral Resources explores mining management-the process of generating plans and supervising their implement.
Keywords: Mines and mineral resources -- Management.; elektronické knihy; electronic books